Percutaneous nephrolithotomy in patients with bleeding disorders: Case report (2019)
Objective To report a case of percutaneous nephrolithotomy in patients with protein C and S deficiency. Introduction Patients with protein C and S deficiency have a high risk of thromboembolic events reporting rates of 6% and 8.4%, respectively. Case Report A 43-year-old female patient with a history of protein C and S deficiency with chronic warfarin anticoagulation for deep venous thrombosis (DVT). CT scan with full right staghorn calculi. Enoxaparin was administered bridge therapy. She was taken to right percutaneous nephrolithotomy, access was through the lower calyx. Because it was not possible to access the calculus of the middle and upper calyx it was necessary to perform a second puncture in the upper calyx, leaving the patient free of calculus. Full anticoagulation was resumed at 12 hours postoperatively without associated bleeding. Discussion Patients with protein C and S deficits are at high risk for thromboembolic events. Kefer et al. conducted a study evaluating the efficacy of bridge therapy in patients on NLP, finding that warfarin anticoagulation can be discontinued 5 days earlier and restarted 5 days after the surgical procedure without the need for enoxaparin bridging therapy. Results The protein C and S deficiency corresponds to an entity, with a very low prevalence and conditions the requirement of oral anticoagulants indefinitely. It was possible to perform a surgical procedure without hemorrhagic or thromboembolic complications. Copyright © 2019, Sociedad Colombiana de Urología.